Managed aquifer recharge shows promise in the Ganges Basin - Pavelic, Paul; Sharma, Navneet; Alam, Faiz; Angou, Gayathri; Ross, Andrew (CGIAR System Organization, 2023)
“Groundwater is the hidden water resource,” says Dr Andrew Ross, an honorary research fellow at the Australian National University’s Fenner School of Environment and Society. “It accounts for more than 99 percent of liquid freshwater on Earth, half of all drinking water and a quarter of the water used for irrigation, serving 38 percent of the world’s irrigated land.” Dr Ross was speaking at the CGIAR Initiative on NEXUS Gains’ latest webinar, Managed Aquifer Recharge in the Ganges Basin: Examining Barriers to Wider Implementation. Held on Thursday, July 27, the webinar explored the potential of underground transfer of floods for irrigation (UTFI), an innovative new form of managed aquifer recharge, to offset aquifer depletion and reduce the severity of both floods and droughts.